Students’ Representation Ability in Chemistry - Dewi Satria Ahmar; Muhammad Fath Azzajjad; Muh. Syahrir (Journal of Applied Science, Engineering, Technology, and Education, 2020)
This study aimed to determine the representation ability of students in learning chemistry. The ability of representation consists of three levels, namely macroscopic level, submicroscopic level, and symbolic level. This study was a descriptive study. The subjects in this study were 53 XI grade students. The study instrument was in the form of a description test compiled based on indicators of representation ability. The results showed that the average score of students’ representation ability at the macroscopic level is 66.94, and is in the good category. The average score of students’ representation ability at the submicroscopic level is 47.17, and is in the medium category. The average score of students’ representation ability at the symbolic level is 64.30, and is in the good category.